The role of grain boundaries in the initial oxidation behavior of austenitic stainless steel containing alloyed Cu at 700 degrees C for advanced thermal power plant applications - Kim, Ju-Heon; Kim, Byung Kyu; Kim, Dong-Ik; Choi, Pytick-Pa; Raabe, Dierk; Yi, Kyung-Woo (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The role of grain boundaries during the early stages of oxidation in austenitic stainless steels containing alloyed Cu was investigated using APT, TEM, EBSD, EPMA, and XRD. The oxidation experiments were performed at 700 degrees C in air with 20% water vapor. Within 4 mu m from the grain boundaries, the oxide layer exhibits a dual-layer structure consisting of a thin Fe-rich spinel oxide on a protective Cr2O3 oxide. Away from the grain boundaries, non-protective spinel oxide layers are formed as the outer and inner oxide layers. A critical grain size that prevents the formation of fast-growing spinel oxides is discussed. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: HIGH-TEMPERATURE OXIDATION; PROBE SPECIMEN PREPARATION; X-RAY-DIFFRACTION; PWR PRIMARY WATER; FE-CR; AISI 304-STAINLESS-STEEL; BREAKAWAY OXIDATION; CORROSION BEHAVIOR; ION-IMPLANTATION; BOILER MATERIALS